Persoalan Iddah dan Ihdad Bagi Wanita Karir - Nurdin (Tadabbur: Jurnal Peradaban Islam, 2021)
The discussion in this study tries to reveal everything related to women's freedom in doing activities outside the home, but she also has several religious regulations that follow and limit. This articel aims to explain the positive legal views towards Iddah and Ihdad career women, and to explain the Islamic legal views towards Iddah and Ihdad career women. The author uses the library research method or library research. Based on the research results, it can be concluded that the stipulation of Iddah and Ihdad laws for women is reasonable, both in terms of religion and in terms of goodness for women. However, several prohibitions for a woman who practices iddah and ihdad can find several reasons to become a law that is appropriate in every era and situation.